The Utilization of Wuluh Starfruit for Making Facial Cleansing Solid Soap - Dian Maulina; Riski Sartika (LPPM Politeknik Aceh Selatan, 2021)
Belimbing wuluh is one of the species in the family (Averrhoa). It is estimated that this plant comes from tropical America, this plant grows well in its country of origin, while Indonesia is mostly kept in the yard and sometimes grows wild in the fields or forest edges. In general, wuluh starfruit for the people of Aceh is used as a spice called sunti acid. Starfruit can also be used as a raw material for making soap which has properties to inhibit premature aging and overcome acne problems because starfruit contains vitamins A and C.Belimbing wuluh is also known as a plant that grows in the yards of Acehnese houses, which every time it bears fruit it will produce quite a lot of fruit, if it is not used for making processed products, the fruit will rot on the tree or fall on the ground. Based on the abundant raw materials, this research will focus on